Genome-wide investigation and expression profiling of LOR gene family in rapeseed under salinity and ABA stress - Yang, Su; Chen, Jialuo; Ding, Yonghe; Huang, Qian; Chen, Guangna; Ulhassan, Zaid; Wei, Ji’an; Wang, Jian (Frontiers in Plant Science, 2023)
The Brassica napus (B. napus) LOR (Lurp-One-Related) gene family is a little-known gene family characterized by a conserved LOR domain in the proteins. Limited research in Arabidopsis showed that LOR family members played important roles in Hyaloperonospora parasitica (Hpa) defense. Nevertheless, there is a paucity of research investigating the role of the LOR gene family towards their responses to hormone induction and abiotic stresses. This study encompassed a comprehensive survey of 56 LOR genes in B. napus, which is a prominent oilseed crop that holds substantial economic significance in China, Europe, and North America. Additionally, the study evaluated the expression profiles of these genes in response to hormone induction and abiotic stresses. Phylogenetic analysis showed that 56 BnLORs could be divided into 3 subgroups (8 clades) with uneven distribution on 19 chromosomes. 37 out of 56 BnLOR members have experienced segmental duplication and 5 of them have undergone tandem repeats events with strong evidence of purifying selection. Cis-regulatory elements (CREs) analysis indicated that BnLORs involved in process such as light response, hormone response, low temperature response, heat stress response, and dehydration response. The expression pattern of BnLOR family members revealed tissue specificity. RNA-Seq and qRT-PCR analyses were conducted to evaluate and validate and the expression pattern of BnLOR genes under hormone induction and abiotic stress, demonstrating that the majority of BnLORs exhibited inducibility under hormone induction and abiotic stress. This study enhanced our comprehension of the B. napus LOR gene family and could provide valuable information for identifying and selecting genes for stress resistant breeding.